A simple method to measure DC electric field with space charges. (4th February 2021) - Zhang, Bo; Meng, Yongchang; He, Jinliang
Abstract: DC partial discharge in gas generates many space charges. Because these charges move with the electric field, change the electric field and accumulate on the surface of sensors, it is difficult to measure the electric field in the space. Based on the relationship between the charge accumulated on the surface of the dielectric in the ion flow field and the applied electric field, this paper proposes a simple method to measure the electric field with space charges using a suspended dielectric as a sensor. By testing the charge accumulated on the suspended dielectric, the applied electric field can be determined. The method is verified and the factors that affect the measurement result are investigated by experiments in a predictable and controllable ion flow field. The results show that when saturation of the accumulation of the space charge on the suspended disc is reached, the total accumulated surface charges are linear with the normal component of the external applied electric field. The ion flow density just affects the speed of the charge accumulation and does not affect the amount of saturated surface charges. The relationship coefficient between the surface charge and the electric field can be obtained through calibration. Unlike other methods that regard the accumulation of charge on the sensor as the key interference, the method in this article just uses the accumulation characteristics of the charge on the sensor, which is simple and feasible.